The WOX family transcriptional regulator SlLAM1 controls compound leaf and floral organ development in Solanum lycopersicum. (5th December 2020) - Wang, Chaoqun; Zhao, Baolin; He, Liangliang; Zhou, Shaoli; Liu, Ye; Zhao, Weiyue; Guo, Shiqi; Wang, Ruoruo; Bai, Quanzi; Li, Youhan; Wang, Dongfa; Wu, Qing; et al.
Abstract : The LAM1 transcription factor regulates expansion of primary leaflets in the compound leaves of tomato, and also affects floral organ development, fruit size, and initiation of secondary leaflets. Abstract: Plant-specific WOX family transcription factors play important roles ranging from embryogenesis to lateral organ development. The WOX1 transcription factors, which belong to the modern clade of the WOX family, are known to regulate outgrowth of the leaf blade specifically in the mediolateral axis; however, the role of WOX1 in compound leaf development remains unknown. Phylogenetic analysis of the whole WOX family in tomato ( Solanum lycopersicum ) indicates that there are 10 members that represent the modern, intermediate, and ancient clades. Using phylogenetic analysis and a reverse genetic approach, in this study we identified SlLAM1 in the modern clade and examined its function and tissue-specific expression pattern. We found that knocking out SlLAM1 via CRISPR/Cas9-mediated genome editing led to narrow leaves and a reduced number of secondary leaflets. Overexpression of tomato SlLAM1 could rescue the defects of the tobacco lam1 mutant. Anatomical and transcriptomic analyses demonstrated that floral organ development, fruit size, secondary leaflet initiation, and leaf complexity were altered due to loss-of-function of SlLAM1 . These findings demonstrate that tomato SlLAM1 plays an important role in the regulation of secondary leaflet initiation, in addition to its conserved function in blade expansion.